A study to correlate association between vitamin D with fibroid and its supplementation in the progression of the disease - Xess, Somila; Sahu, Jaiprakash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Uterine fibroids, or leiomyomas are the most common benign tumors of the female reproductive tract, affecting up to 60% of Indian women with only 25% of women who are symptomatic. Symptoms do not always correlate with the size, number, or location of the fibroids. Recent studies suggest that hypovitaminosis D is associated with an increased risk of uterine fibroids. Methods: Total 110 women diagnosed with fibroid in USG were included in the study. Inclusion and exclusion criteria were applied and size of the fibroid noted. 60 women were included in the study group who took Vitamin D supplementation and 50 women in the control group who didn’t perform the study properly. Results: The growth pattern of fibroids with study group under supplementation with 25-OH-D3 seems to be stable, with no increases or decreases in size or number of identified lesions. Instead, women in control group, who did not perform appropriate vitamin D supplementation seem to have a slight but significant increase in size of the lesions. Conclusions: It was seen that hypovitaminosis D was associated with fibroid and thus supplementation with Vitamin D helped in the shrinkage of fibroid or slower the progression of the disease.